Énergies renouvelables et coopération transfrontalière : la gouvernance multi-niveaux du processus de planification énergétique - Melis Aras (VertigO)
In accordance with commitments made at the international (Paris Climate Agreement) and European (Clean energy for all Europeans package) level, the climate emergency requires not only promoting the production of electricity from renewable energy sources (RES) in order to reduce greenhouse gas (GHG) emissions, but also enhancing the potential for cooperation between all stakeholders, including Member States, local authorities and citizens, for both common (European) and decentralized action. The European strategy for an “Energy Union”, which reaffirms the need to use RES, considers cross-border cooperation as one of the vehicles for the European energy transition. However, cross-border cooperation in renewable energy requires a review of the energy planning process, as well as of the existing modes of governance due to the multiplication of actors in the decision-making process, and the emergence of new conditions and methods serving as coordination mechanisms between them. This article reviews the institutional framework of the RES development planning process and seeks to clarify the forms of governance present at different territorial scales. Adopting the traditional approach based on the legal analysis of regulations at the supranational and national level, and in light of the current legal framework in France, the aim of this article is also to demonstrate the extent to which cross-border cooperation in the European context of energy transition is a reality.